Assessment of sexual dysfunctions among newly married couples in Egypt: a case-control study - Essam El-Den Mohamed Mohamed; Hazem L Abdel-Aleem; Ahmed G Hamdy (Wolters Kluwer Medknow Publications, 2021)
Background and Aim Unconsummated marriage is a problem among couples who are not able to perform natural sexual intercourse. The aim of this work was to define the etiological factors of unconsummated marriage in newly married men. Patients and methods This is a case-control study that was carried out on 200 newly married men during the period between October 2019 and October 2020, comprising 100 men with sexual dysfunctions leading to unconsummated marriage as a case group and 100 men without any sexual dysfunctions having successful intercourse as a control group. They were evaluated through history taking, psychosexual questionnaires, general and local examinations, laboratory investigations (estimations of serum serum total and free testosterone, estradiol, prolactin, luteinizing hormone, follicle-stimulating hormone, fasting and postprandial blood glucose levels, and lipid profile), and penile duplex. Results Regarding sexual history, male c ause of unconsummated marriage was present in 82% of the patients in the form of erectile dysfunction (73% psychogenic and 9% organic, using penile dupplex), and the other 18% of the patients had history of female cause in the form of vaginismus. Psychosexual history showed that history of consulting scientific informative source concerning sexuality was present in only 3% of patients, history of refusing to look closely at the partner's genitalia was present in 4%, and history of being afraid of feeling pain during penetration was present in 9%. Conclusion Psychogenic erectile dysfunction was the most common etiological factor for unconsummated marriage. Vaginismus was found to be a major concern regarding unconsummated marriage as well. Lack of scientific information about sexuality was found to be a major risk factor for unconsummated marriage in newly married men.